Experimental induction of delay union in femur bone fracture and itseffect on the adjacent skeletal muscles - Ismael Seddeek , Ban (Tikrit Journal of Pharmaceutical Sciences, 2023)
Bone fracture and its healing process have been extensively investigated for many years. in this stady bone delayed .union and its effect on the adjacent muscle was investigated. Ten local breed adult rabbits of both sexes weighing 1200-1500 g were used in the experiment. All animals were undergoing surgical operations to induce a transverse closed fracture in the midshaft of the femur, All animals were survived for five months' and then killed using high dose inhalation of chloroform inside glass box. The surgical procedures were made under (general anesthesia) of 50mg/kg Ketamin hydrochloride. A 5 cm longitudinal incision was made on the lateral side of the right thigh. the fractured bone were fixed using intramedullary fixati.on). Approximate the two fragments and a gap of about 2.5-3 mm length was left to prevent normal bone union. The length and weight of each muscle were measured. Comparison between right and left side for both weight and length was made. A specimen from the muscles of anterior group of thigh (i.e. Rectus femoris), posterior group of thigh (i.e. biceps femoris), anterior group of leg (i.e.tibialis anterior), and posterior group of leg (i.e. soleus) for both right and left was taken. Sample also from fracture site was taken. Staining of sections using Haematoxylin and eosin.the result revealed a significant decrease in muscle fibers weight and diameters. It was concluded that the delay in bone healing reflected on recovery of the weight and diameter of adjacent skeletal muscle fibers.